Oxygen mass transfer to emulsions in bubble column contactor - Gómez-Díaz, Diego (2007)
Present work includes an exhaustive study about the oxygen absorption process by the analysis of volumetric mass transfer coefficient and the corresponding value of interfacial area between gas phase and liquid heterogeneous medium generated in a rectangular bubble contactor. The system studied has been composed by water, methyl ricinoleate and Tween 80, since it is the base of the medium used for an aroma production from the biotransformation of ricinoleic acid by the yeast Yarrowia lipolytica.